PENERAPAN NILAI PENDIDIKAN KARAKTER MELALUI KAJIAN TA’LIMUL MUTA’ALLIM DI MAN 2 JOMBANG - Dewi, Litasari Ratna (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
In this research, the approach used by researchers is qualitative because in this research there are no calculations, natural research, and symbolic interactions. The instruments used are documentation and observation. Extended observation, triangulation, increased persistence, analysis of negative cases, using reference materials, and member checking are some methods to ensure data validity. Meanwhile, data reduction, data presentation, and data verification are the data analysis methods used. The problems examined in this research are: 1) How is the book Ta'limul Muta'allim taught at MAN? 2) What are the efforts to apply the value of character education in learning the book Ta'limul Muta'allim at MAN? Based on research findings, Ta'limul Muta'allim, studied at MAN as a method of imparting knowledge in general, is in line with the important role of the book. The teacher's main responsibility is to process, plan, assess and guide teaching and learning activities as effectively as possible while getting to know their students and all their qualities. They also have to know what needs to be achieved after the learning process to create a positive experience. Furthermore, efforts to instill values ​​related to character education by studying the book Ta'limul Muta'allim at MAN are carried out both directly and indirectly, through activities outside of learning such as recitation in the month of Ramadhan, through exemplary techniques, guidance and attention, as well day of habituation.